2014
DOI: 10.1128/aem.02568-14
|View full text |Cite
|
Sign up to set email alerts
|

PCR and Culture Identification of Pathogenic Leptospira spp. from Coastal Soil in Leyte, Philippines, after a Storm Surge during Super Typhoon Haiyan (Yolanda)

Abstract: e Leptospirosis is a zoonosis caused by pathogenic Leptospira spp. Most of the outbreaks of leptospirosis occur after floods caused by heavy rain in countries where Leptospira spp. are endemic. It has been believed that the overflow of seawater rarely causes outbreaks of leptospirosis because the leptospires are killed by salt water. On 8 November 2013, a storm surge caused by Super Typhoon Haiyan (Yolanda) inundated the entire coastal areas of Tacloban and Palo in Leyte, Philippines. The present study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 19 publications
(22 reference statements)
3
82
1
Order By: Relevance
“…The DNA of the pathogenic Leptospira was confirmed in the soil of the coastal area in the Philippines after a storm surge, indicating that the soil can be a breeding ground for Leptospira during a disaster and the agents can survive in seawater (Saito et al 2014). Although historical huge tsunami hit the east coastline of the Tohoku region in March 11, 2011, the patients of leptospirosis were not found (National Epidemiological Surveillance of Infectious Diseases (NESID)).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA of the pathogenic Leptospira was confirmed in the soil of the coastal area in the Philippines after a storm surge, indicating that the soil can be a breeding ground for Leptospira during a disaster and the agents can survive in seawater (Saito et al 2014). Although historical huge tsunami hit the east coastline of the Tohoku region in March 11, 2011, the patients of leptospirosis were not found (National Epidemiological Surveillance of Infectious Diseases (NESID)).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 5 isolates (5 17, 29 ) were found to be closely related to L. alstonii with 99 to 100 identity, whereas 1 isolate (1 17, 6 ) is closely related to L. kmetyi, with 99 identity. The presence of L. alstonii and L. kmetyi in the environment has been reported in many countries (7)(8)(9)(10). Recently, L. alstonii was isolated from greater white toothed-shrews in Ireland (11) and from an asymptomatic cow in a slaughter house in Brazil (12).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that leptospires are ubiquitous in the Philippines and are soil bacteria. Based on the results of this recent study, it was hypothesized that soil serves as an important reservoir of pathogenic Leptospira spirochetes, which may cause outbreaks of leptospirosis during floods caused by typhoons and/or heavy rains (Saito et al 2014). Therefore, it is expected that walking through mud without protective footwear (for example, during farm work, water-based recreation, or wading after a flood) would place a person at high risk for acquiring infection with Leptospira.…”
Section: Emerging Zoonosis In Global Warmingmentioning
confidence: 99%